The utility of a 'non‐significant' coronary angiogram. Issue 12 (25th August 2015) - Wang, T. K. M.; Oh, T. H. T.; Samaranayake, C. B.; Webster, M. W. I.; Stewart, J. T.; Watson, T.; Ellis, C.; Ruygrok, P. N.
Summary: Background: Coronary angiography is the gold standard for assessing coronary artery disease (CAD). In many patients with chest pain, no or mild CAD (< 50% stenosis) is found. It is uncertain whether this 'non‐significant' result influences management and outcomes. We reviewed characteristics and outcomes in a contemporary cohort of chest pain referrals who had mild or absent CAD on coronary angiography. Method: All patients undergoing coronary angiography at Auckland City Hospital during July 2010–October 2011 were reviewed ( n  = 2983). Of these, 12.3% ( n  = 366) underwent coronary angiography for evaluation of chest pain and were found to have absent or mild CAD. These patients were followed up for 2.3 ± 0.6 years. Results: Mean age was 60.0 ± 12.3 years, 56.1% were female. The ECG was abnormal in 55.0% of patients. Stress testing for inducible ischaemia was undertaken in 40.7% of patients and was abnormal in 57.7%. Following angiography, 43.2% had no changes to cardiac medications. Additional drug therapy (aspirin, statin, beta‐blockers, ACE‐inhibitor) was commenced in around 14.2–22.1% of cases. These drugs were discontinued in 4.1–8.2% of patients. Rates of major adverse cardiovascular events and readmissions with chest pain were 0.3% (1) and 1.9% (7) respectively at 30 days, and 1.9% (7) and 6.0% (22) at 1 year. Conclusion: Although even non‐obstructive atheroma may justify medical therapy to limit disease progression, our findings may suggest that in these cases, invasive coronary angiography, may not lead to the patient/physician reassurance justified by historical data.